Dreaming - Hobson, J. Allan (Oxford University Press, 2002)
What is dreaming? Why are dreams so strange and why are they so hard to remember? In this fascinating book, Harvard researcher Allan Hobson offers an intriguing look at our nightly odyssey through the illusory world of dreams